Penerapan Agile Project Management Pada Pembuatan Sistem E-Warga Taman Cibodas Lippo Cikarang - Andre Elmustanizar (FKOM UNIKU, 2022)
The application of E-Government technology in the government at this time has not been applied evenly across the region, particularly in the lowest levels, i.e., RT (Rukun Tetangga). The current activities of administrative services in the region of RT001/RW017 Perumahan Taman Cibodas Lippo Cikarang, still using the conventional methods. By utilizing a technology system, namely E-Warga, is expected to change the way that still conventional to be automatic and more efficient. By using the method of Agile Management System Scrum model and using the PHP programming language using the Laravel Framework and MySql database, the process of making the system of E-Warga this will be faster, because it divides the project into several parts called sprint. The results of the study showed that the processing time of the system E-Warga takes 8 weeks by dividing the project into 5 sprint. Evaluation of the results of the sprint is done after completing the work of 1 sprint that has been determined the scale of the priority previously. With the presence of a system of E-Warga, then the expected that RT administrators and residents in the territory of RT001/RW017 Perumahan Taman Cibodas Lippo Cikarang, can carry out administrative activities efficiently and more quickly than ever before.